Building Indonesia’s Golden Generation 2045: Fostering Financial Literacy and Information Technology Competencies in SMAN 1 Indralaya - Eogenie Lakilaki (JURNAL ABDIMAS MADUMA, 2025)
Currently digital economy, proficiency in artificial intelligence (AI), digital technologies, and personal finance is essential. This community engagement initiative at SMAN 1 Indralaya integrated AI, digital, and financial literacy training through a four-stage framework: needs assessment, instructional delivery, technical mentoring, and evaluation. The programme significantly improved students’ ethical digital awareness, practical use of AI tools for budgeting, and basic financial reporting skills. The spontaneous formation of peer-learning groups indicated a shift toward autonomous, sustainable learning. These outcomes affirm the effectiveness of AI-integrated pedagogies in cultivating future-ready competencies in under-resourced educational settings.